Train - Coiley, John.; Dunning, Mike (New York : Distributed by Random House, 1992)
Traces the development of railways from the first Babylonian rutways to the electromagnetic, driverless trains of today and describes how trains are built and operated.
"A Dorling Kindersley book"--T.p. verso.
Includes index.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.6
Keywords: Railroads -- Juvenile literature; Railroads; Railroads